M. Veller’s “The Great Last Chance”: Russian National Myths, Ideas, and Author’s View on the Problems - Perov, Oleg (Respectus Philologicus, 2015)
This article presents the analysis of the main ideas which are reflected in M. Veller’s novel The Great Last Chance. This is not only a reception of a definite country, a version of her historical way, the demonstration of cultural peculiarities, the own code of civilization, people’s traditions and faith, but also an original author’s view on the process of self-identification and logical result, i.e., the national myths and ideas. The main intention is to negotiate, refute many national myths: about complicated and bloody history; about laziness and hard drinking; about the opposition of East and West; about the peace-loving nation; about the underestimation from the other world. The author asserts that the Russian national idea is not liberal: the main basis is a national self-identification, the main traits are social justice and retribution for guilty. The main problems of the country are located in a definite range: from the global to the local (stealing, corruption, negative information field). The principal way to solve these problems is to aspirate to the social justice, labour, and creative works.
Keywords: Culture; National Myth; Code of Civilization; Social Justice